Quranic interpretation of tawakkul: Enhancing mental health among working women in Malaysia - Abdul Khalid, Nur Alia Arisya; Abd Kadir, Kauthar (Journal of Islamic, Social, Economics and Development, 2025)
This study examines the concept of Tawakkul (trust in Allah) as interpreted in the Quran and its impact on the mental health of working women in Malaysia. Work–family role conflicts are a common source of stress that can affect women’s psychological well-being. The objective of this study is to investigate the relationship between Tawakkul and mental health, and to analyze how this concept can help women manage life stress. A qualitative approach was employed by analyzing secondary data from academic articles, Quranic exegesis, and relevant reports. Thematic analysis identified key themes such as emotional resilience, patience, and reliance on Allah. The findings indicate that Tawakkul enhances emotional resilience and helps alleviate stress, enabling women to manage work–family conflicts with greater composure. In conclusion, Tawakkul serves as a significant Islamic value-based approach to supporting the mental health of working women in Malaysia and should be considered in the development of more holistic mental health intervention programs.